2011
DOI: 10.1161/hypertensionaha.110.164244
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Angiotensin II–Mediated Renal Oxidative Stress, Inflammation, and Fibrosis by Angiotensin-Converting Enzyme 2

Abstract: Angiotensin-converting enzyme 2 (ACE2) is a monocarboxypeptidase capable of metabolizing angiotensin (Ang) II into Ang 1 to 7. We hypothesized that ACE2 is a negative regulator of Ang II signaling and its adverse effects on the kidneys. Ang II infusion (1.5 mg/kg⁻¹/d⁻¹) for 4 days resulted in higher renal Ang II levels and increased nicotinamide adenine dinucleotide phosphate oxidase activity in ACE2 knockout (Ace2(-/y)) mice compared to wild-type mice. Expression of proinflammatory cytokines, interleukin-1β a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
192
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(210 citation statements)
references
References 60 publications
13
192
1
4
Order By: Relevance
“…[24][25][26] The functional importance of Ace2 is now established by recent findings that loss of Ace2 promotes but administration of recombinant human ACE2 inhibits exogenous Ang II-induced hypertensive nephropathy and streptozotocin-induced diabetic nephropathy. [8][9][10][11]27 All these findings imply that Ace2 may protect against progressive renal injury in diseases associated with hypertension and diabetes. In the present study, we found that disruption of Ace2 largely enhanced intrarenal Ang II levels (a twofold Ace2 protects renal fibrosis and inflammation Z Liu et al increase), which was accompanied by much more severe renal fibrosis and inflammation, demonstrating a renoprotective role for Ace2 in obstructive nephropathy.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…[24][25][26] The functional importance of Ace2 is now established by recent findings that loss of Ace2 promotes but administration of recombinant human ACE2 inhibits exogenous Ang II-induced hypertensive nephropathy and streptozotocin-induced diabetic nephropathy. [8][9][10][11]27 All these findings imply that Ace2 may protect against progressive renal injury in diseases associated with hypertension and diabetes. In the present study, we found that disruption of Ace2 largely enhanced intrarenal Ang II levels (a twofold Ace2 protects renal fibrosis and inflammation Z Liu et al increase), which was accompanied by much more severe renal fibrosis and inflammation, demonstrating a renoprotective role for Ace2 in obstructive nephropathy.…”
Section: Discussionmentioning
confidence: 93%
“…Loss of Ace2 leads to the late development of glomerulosclerosis by 12 months of the age, and accelerates kidney injury in mouse models of diabetes and Ang II infusion. [7][8][9] ACE2 inhibits progression of diabetic kidney disease clearly demonstrated a renoprotective role for ACE2 in the progression of chronic kidney diseases. 10 All these studies suggest a negative regulatory role for ACE2 in blood pressure and Ang II-mediated hypertensive and diabetic nephropathy.…”
mentioning
confidence: 99%
“…Besides its physiological relevance for kidney homeostasis, the ACE2/Ang-(1-7)/Mas axis also has an important and controversial role in renal diseases, acting as a renoprotective (Oudit et al 2006, 2010, Soler et al 2007, Pinheiro et al 2009, Burns et al 2010, Dilauro et al 2010, Zhang et al 2010, Giani et al 2011, Liu et al 2011b, Moon et al 2011, Stegbauer et al 2011, Zhong et al 2011, Barroso et al 2012, Kim et al 2012, Nadarajah et al 2012 or a proinflammatory (Esteban et al 2009, Velkoska et al 2011 agent. Briefly, Pinheiro et al (2009) reported that mice with genetic deletion of Mas developed renal dysfunction with an increase of glomerular tuft diameter and enhancement of fibronectin and collagen IV and III deposition, besides an increase of AT 1 and TGF-b expression.…”
Section: Vascular Actions Of the Ace2/ang-(1-7)/mas Axismentioning
confidence: 99%
“…glomerular mesangial matrix, smooth muscle actin and collagen III expression in diabetic AKITA mice (Oudit et al 2010) and in wild-type mice infused with Ang II (Zhong et al 2011). Accordingly, knockout mice for ACE2 infused with Ang II showed enhanced collagen I deposition and expression of genes related to fibrosis, such as smooth muscle actin, TGF-beta, and procollagen I, probably through activation of ERK1/2 and enhancement of protein kinase C levels (Zhong et al 2011). Taken together, these data suggest that renal pathogenesis is driven by a disruption in the ACE-ACE2 balance.…”
Section: Vascular Actions Of the Ace2/ang-(1-7)/mas Axismentioning
confidence: 99%
“…Previous in vivo studies have shown that the elevation of Ang II by chronic infusion results in renal fibrosis, which is associated with expression of proinflammatory cytokines and fibrosis-associated genes [13] . Ang II is one of the main pathogenic mediators of renal interstitial fibrosis, especially in obstructive nephropathy [10][11][12]14] .…”
Section: Introductionmentioning
confidence: 99%